Risk Factors for Predicting Mortality and Amputation of Patients with Necrotizing Soft-Tissue Infections: Retrospective Analysis of 111 Cases from a Single Medical Center - Cen, Hanghui; Jin, Ronghua; Yin, Jun; Wang, Xingang (Emergency Medicine International, 2023)
Objective. Necrotizing soft-tissue infections (NSTIs) are rare clinical infections with surgical emergencies having a high mortality rate. This study aimed to investigate risk factors for mortality and amputation of patients with NSTI. Methods. We retrospectively analyzed critical factors for outcomes of 111 patients with NSTI hospitalized in our department from 1 January 1999 to 31 December 2018. NSTI diagnosis was based on the patient’s clinical characteristics, laboratory risk indicator for necrotizing fasciitis (LRINEC) score, laboratory test data, and microbiological findings in blood and wound culture. The risk factors for mortality and amputation of NSTI were determined using univariate or multivariate logistic regression analysis, receiver operating characteristics (ROC), and the area under the ROC curve (AUC) at 90 days after admission. Results. Diagnosis of 111 patients with NSTI was confirmed according to clinical features, LRINEC score, image data, laboratory findings, and microorganism culture in blood and wounds. The mortality rate was 9.91% (11/111) at day 90 follow-up. High white blood cell (WBC), low hematocrit (HCT), and multiple surgeries were identified to be critical risk factors for NSTI mortality in univariate and multivariate logistic analyses. AUCs, 95% confidence intervals (CI), and P values of risk factors were 0.699, 0.54–0.95, and P=0.0117 for high WBC; 0.788, 0.63–0.97, and P=0.0006 for low HCT; and 0.745, 0.59–0.90, and P=0.0018 for multiple surgeries, respectively. These patients also had high LRINEC scores. Amputation occurred in 34.23% (38/111) of patients. Risk factors for amputation were higher age, low hemoglobin (Hb), and multiple wounds. AUCs, 95% confidence intervals (CI), and P values were 0.713, 0.11–0.32, and P<0.0001 for higher age; 0.798, 0.08–0.29, and P=0.0007 for low Hb; and 0.757, 0.17–0.34, and P <0.0001 for multiple lesion sites, respectively. Conclusions. High LRINEC scores, high WBC, low HCT, and multiple surgeries were relevant to increased mortality. Higher age, low Hb, and multiple wounds were associated with amputation risk. These clinical features must be paid attention to when patients are diagnosed with NSTI.